2017
DOI: 10.1002/2017je005276
|View full text |Cite
|
Sign up to set email alerts
|

The stratigraphy and history of Mars' northern lowlands through mineralogy of impact craters: A comprehensive survey

Abstract: The basin‐filling materials of the northern lowlands, which cover approximately one third of Mars' surface, record the long‐term evolution of Mars' geology and climate. The buried stratigraphy was inferred through analyses of impact crater mineralogy, detected using data acquired by the Compact Reconnaissance Imaging Spectrometer for Mars. Examining 1045 impact craters across the northern lowlands, we find widespread olivine and pyroxene and diverse hydrated/hydroxylated minerals, including Fe/Mg smectite, chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 116 publications
4
76
0
1
Order By: Relevance
“…The possible existence of hydrated minerals buried under several kilometers of unaltered material in the northern lowlands (Pan et al, 2017) is consistent with the proposed period of widespread aqueous interaction and alteration that formed both the present southern highlands soil and the possibly buried paleosol in the northern lowlands. In addition, such widespread aqueous processes and soil alteration can create biologically significant redox-sensitive minerals.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The possible existence of hydrated minerals buried under several kilometers of unaltered material in the northern lowlands (Pan et al, 2017) is consistent with the proposed period of widespread aqueous interaction and alteration that formed both the present southern highlands soil and the possibly buried paleosol in the northern lowlands. In addition, such widespread aqueous processes and soil alteration can create biologically significant redox-sensitive minerals.…”
Section: Discussionsupporting
confidence: 80%
“…Minerals produced by these processes (e.g., perchlorates and Mg-sulfates) are typically soluble or deliquescent, and the preservation of such phases over geologic time in the near surface necessitates low water-to-rock ratios (e.g., Kounaves et al, 2010). This history is consistent with recent evidence from mineralogical observations (Pan et al, 2017) suggesting that much of the upper (<2 km) volcanic or volcaniclastic rock in the northern lowlands lacks signatures of significant alteration. Relative quiescence of widespread aqueous process and limited soil redistribution since the Hesperian would allow the poorly altered soil at the surface of the northern lowlands to arise from physical weathering of the underlying material with limited chemical weathering.…”
Section: Cumulative Pca Resultssupporting
confidence: 67%
“…Spatial mixing with nearby chlorite is a possible explanation of the strong 2.35-μm feature, often equivalent to or stronger than the 2.21-μm feature. Illite/muscovite has been identified previously in the southern highlands (Carter et al, 2013;Ehlmann et al, 2009;Fraeman et al, 2009) and often co-occurs with chlorite minerals (e.g., Ehlmann et al, 2009), but within the northern lowlands, it is only found to occur in the Lyot vicinity (Carter et al, 2013;Pan et al, 2017).…”
Section: Spectral Properties and Distribution Of Hydrous Mineralsmentioning
confidence: 91%
“…The vicinity of Lyot crater has been found with spectral signatures consistent with spatially concentrated exposures of diverse hydrous minerals relative to the entire northern lowlands (Pan et al, 2017), including phases in addition to chlorite-prehnite detections mapped by Carter et al (2010). Here we specifically investigate the spatial distribution of these hydrous minerals and relationships with previously identified waterrelated surface features in the vicinity of Lyot, examining whether their origins are related.…”
Section: Introductionmentioning
confidence: 93%
“…(Head ) In contrast to Earth's oceans, which have been present continuously since >4 Ga, Mars may have had an episodic northern ocean fed by outflow channels (e.g., Tanaka ), but there is scant geologic evidence that Mars had a northern ocean in continuous existence for billions of years (e.g., Pan et al. ). However, groundwaters may have been persistent over greater time periods (e.g., Martin et al.…”
Section: Objective 1: Interpret the Primary Geologic Processes And Himentioning
confidence: 99%